2000
DOI: 10.1177/00220345000790110701
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Osseous Implants Having Different Surface Topographies in Rats

Abstract: Biomechanical and biological factors can co-dependently influence the establishment of implant-tissue integration; thus, concurrent evaluation of these factors should provide a better understanding of osseointegration. This study aimed to establish and validate an in vivo rat model frequently used in molecular/cellular biology for implant biomechanical studies. We tested the hypotheses that the implant push-in test assesses the degree of osseointegration by the breakpoint load at the implant-tissue interface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
170
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(183 citation statements)
references
References 25 publications
10
170
1
2
Order By: Relevance
“…NaOCl-mediated enhanced osteoconduction appeared to accelerate bone formation around the implants, which eventually could prevent implant failure. Morphologic and elemental analyses of the tissue remnant on implants retrieved from the femur after the push-in test were previously reported as a useful means to evaluate the quality of osseointegration and fracture behavior at the bone-implant detachment surface 19) . SEM images of retrieved implants indicated that the NaOCl-treated implant surfaces were more extensively covered with mineralized tissue than the untreated implant surfaces for both the polished and acid-etched implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NaOCl-mediated enhanced osteoconduction appeared to accelerate bone formation around the implants, which eventually could prevent implant failure. Morphologic and elemental analyses of the tissue remnant on implants retrieved from the femur after the push-in test were previously reported as a useful means to evaluate the quality of osseointegration and fracture behavior at the bone-implant detachment surface 19) . SEM images of retrieved implants indicated that the NaOCl-treated implant surfaces were more extensively covered with mineralized tissue than the untreated implant surfaces for both the polished and acid-etched implants.…”
Section: Discussionmentioning
confidence: 99%
“…The detached implants were carefully removed from the bone/implant complexes for the assessment of the morphology and quality of bone formed around the implants 19,20) . The specimen was soaked in water under agitation for 1 h and dried at 35°C under reduced pressure.…”
Section: Morphology and Quality Of Bone Formed Around The Implantsmentioning
confidence: 99%
“…It has been reported that sandblasted and acid-etched (SLA) titanium promotes greater osseous contact compared with titanium-plasmasprayed implants [6][7][8][9] . This is due to the high surface roughness of SLA produced by grit blasting and acid etching, with the latter resulting in an increase in sub-surface hydrogen concentration and the formation of titanium hydride 10) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have attempted to increase surface roughness using various surface modifying techniques. Many reports have shown that the bone-implant adhesive strength was enhanced by increasing the surface roughness 23) . From our results it was confirmed that surface roughness was increased using these modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Animal surgery and measurements of bone-titanium integration were performed as described previously 23) . After a 2-week healing period, femurs containing the cylindrical implants were harvested and embedded into an autopolymerizing resin with the top surface at the implant level.…”
Section: Biomechanical Evaluation Of Coated Surfacesmentioning
confidence: 99%